Help Seeking Attitudes Among Cambodian and Laotian Refugees: Implications for Public Mental Health Approaches - Thikeo, Manivone; Florin, Paul; Ng, Chee (Journal of immigrant and minority health, 2015)
This is a pilot study of demographic and acculturation factors in relation to attitudes toward seeking psychological help among Lao and Cambodian refugees and immigrants in the United States of America. Cambodian and Laotian American adults in the United States of America were approached to complete help-seeking attitudes and acculturation scales. T test and hierarchical multiple regression analyses were used to analyze the relationships between the demographic and acculturation variables, and attitudes toward seeking psychological help. Out of 270 target subjects approached there were 108 respondents. Of the demographic variables, gender was associated with favorable attitudes towards psychological help-seeking. As expected, women were significantly more likely than men to recognize the need for help, to seek psychological help, to be more open to discussing mental health problems, and have more confidence in professional services. Acculturation was more powerfully associated with help- seeking attitudes than any of the demographic variables. In hierarchical multiple regression, acculturation contributed significant unique variance over and beyond the entire set of demographic variables to openness to discussing problems and having confidence in professional help. The findings of this pilot study suggest that there are significant barriers to seeking psychological help among Lao and Cambodian Americans. Attention to the issues of gender and levels of acculturation may improve access.